2014
DOI: 10.1111/ene.12534
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteomic analysis of a pre‐symptomatic multiple sclerosis cohort

Abstract: Compared with healthy controls, differential proteomic changes were noted in the serum of patients with MS that preceded the onset of symptomatic disease. Further work is in progress to confirm or refute these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
1
17
2
Order By: Relevance
“…Complement activation is a well‐known feature in gray matter lesions, these lesions were surrounded by complement receptor‐positive microglia, and known to contribute to irreversible MS progression . Additionally, the presence of C3 together with other complement factors, and Fibronectin aggregates at lesions have been shown to prevent remyelination and shown to be differentially regulated in serum of presymptomatic and symptomatic MS patients . We observed a significant increase of C3 plasma levels related to increasing brain atrophy and increased FN1 plasma levels in RO‐all compared to healthy controls.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Complement activation is a well‐known feature in gray matter lesions, these lesions were surrounded by complement receptor‐positive microglia, and known to contribute to irreversible MS progression . Additionally, the presence of C3 together with other complement factors, and Fibronectin aggregates at lesions have been shown to prevent remyelination and shown to be differentially regulated in serum of presymptomatic and symptomatic MS patients . We observed a significant increase of C3 plasma levels related to increasing brain atrophy and increased FN1 plasma levels in RO‐all compared to healthy controls.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous MS biomarker studies performed mostly LC‐MS blood proteomics . Moreover, few studies have focused on the different progression courses within MS, making comparison with earlier publications challenging . Nonetheless, some of our results coincide with earlier findings from candidate approach and pathology based studies, as we will discuss below.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, a more careful examination of the regulated pathways could reveal new therapeutic targets. Interestingly, a recent study using presymptomatic and postsymptomatic sera demonstrated that some proteins were differentially regulated in presymptomatic multiple sclerosis samples compared with the control samples . These data suggest that there are abnormalities even before the onset of symptoms.…”
mentioning
confidence: 98%
“…Multiple sclerosis (MS) is a field of neurology that has undergone tremendous advances within only the last 15 years . The advent of immunological therapies has transformed outcome for patients with relapsing−remitting disease, although the effect on chronic progressive disease is less certain.…”
mentioning
confidence: 99%